High refractive index (Dy) doped (GeTe2)80(In2Te3)20 thin films for sub-THz and millimeter-wave applications. Issue 24 (15th December 2021) - Sharda, Sunanda; Sharma, Ekta; Aly, K.A.; Dahshan, A.; Sharma, Pankaj
Abstract: Chalcogenide materials are ideal for IR applications because of their wide transmission window, variable bandgap, and high nonlinearity. In this regard, optical characteristics of ( Dy ) doped ( GeTe 2 )80 ( In 2 Te 3 )20 thin films have been measured and investigated. The influence of annealing on the optical characteristics of thin films has been reported. The reflectance and transmittance spectra were used to calculate the refractive index ( n ) and extinction coefficient ( k ) of thin films. With the annealing of as-prepared film, the penetration depth (Δ) measured at a wavelength of 1.1 μm and bandgap ( E g ) decrease. The relaxation process has been realized using electric modulus ( M ) determination, and the dielectric loss has been estimated in terms of loss tangent (tan δ). Wemple Di-Domenico (WDD) model has been employed to calculate dispersion energy ( E d ) and average energy gap ( E 0 ). Using the values of E 0 and E d, the static refractive index ( n 0 ) and the moments ( M -1, M -3 ) of the optical spectra have been determined. Sellmeier oscillator parameter ( λ 0 ) increases while S o decreases with a rise in the annealing temperature.